Job Burnout Among Family Physicians in Rural Areas of Isfahan Province - Neda Moein; Gholamhossein Ahmadzadeh; Alireza Safaeeyan (Baqiyatallah University of Medical Sciences, 2018)
Background: In providing optimum medical and health services, great pressure is put on the physical and mental health of family physicians. Job burnout is damaging to the health of family physicians and medical treatment personnel. It leads to reduced job productivity, increased absenteeism, increased healthcare costs, elevated turnover rates, a reduced level of service provided to patients, and ultimately, patient dissatisfaction. Objective: The current research investigated job burnout among family physicians in rural areas of Isfahan province during the years 2017-2018. Methods: This cross-sectional study was carried out in Isfahan province during the years 2017-2018. The research population included all family physicians working in Isfahan province, and 155 of whom met the inclusion criteria and participated in this research. Questionnaires were used as the data collection tool. Data was analyzed using SPSS software, and the analytical variables were analyzed using the independent t test and Pearson correlation coefficient. Results: A total of 45 men (29%) and 110 women (71%) comprised the research population. Participants' mean age and mean duration of work experience were 35.3±8.1 and 7.5 years, respectively. The scores for overall job burnout, emotional exhaustion, depersonalization, and lack of personal accomplishment dimensions were low among the family physicians in Isfahan. The results showed no significant difference between male and female, single and married participants in any of the dimensions. The results also revealed a direct relationship between years of work experience and the overall job burnout and lack of personal accomplishment scores. Conclusion: According to the findings of the present research and considering the stressful nature of a family physician's job, healthcare authorities need to pay special attention to job burnout and implement measures to prevent it or at least reduce its subsequent adverse effects.